Crystallography of the martensitic transformation between Ni2In-type hexagonal and TiNiSi-type orthorhombic phases. (30th March 2022) - Zhang, Tingting; Gong, Yuanyuan; Wang, Bin; Cen, Dongyu; Xu, Feng
Highlights: A bulk sample with small amounts of orthorhombic phases distributed in hexagonal matrix is obtained. The orientation relationship between hexagonal and orthorhombic structures is [ 4 2 ¯ 2 ¯ 3 ] h / / [ 120 ] o & ( 01 1 ¯ 0 ) h / / ( 001 ) o . The habit plane of the hexagonal-orthorhombic transformation is 2 ¯ 1 1 3.26 h . The strain that induce the transformation from hexagonal to orthorhombic structures is revealed. Abstract: MnMX (M = Co or Ni, X = Si or Ge) alloys, experiencing structural transformation between Ni2 In-type hexagonal and TiNiSi-type orthorhombic phases, attract considerable attention due to their potential applications as room-temperature solid refrigerants. Although lots of studies have been carried out on how to tune this transformation and obtain large entropy change in a wide temperature region, the crystallography of this martensitic transformation is still unknown. The biggest obstacle for crystallography investigation is to obtain a bulk sample, in which hexagonal and orthorhombic phases coexist, because the MnMX alloys will fragment into powders after experiencing the transformation. For this reason, we carefully tune the transformation temperature to be slightly below 300 K. In that case, a bulk sample with small amounts of orthorhombic phases distributed in hexagonal matrix is obtained. Most importantly, there are no cracks between the two phases. It facilities us to investigate the microstructure using electron microscope. The obtained results indicate that the orientation relationship between hexagonal and orthorhombic structures is [ 4 2 ¯ 2 ¯ 3 ] h / / [ 120 ] o & ( 01 1 ¯ 0 ) h / / ( 001 ) o and the habit plane is 2 ¯ 1 1 3.26 h . WLR theory is also adopted to calculate the habit plane. The calculated result agrees well with the measured one. Our work reveals the crystallography of hexagonal-orthorhombic transformation for the first time and is helpful for understanding the transformation-associated physical effects in MnMX alloys. Graphical abstract: Image, graphical abstract